2019
DOI: 10.1080/03004430.2018.1564917
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of preschool children’s speech and language skills

Abstract: Many children in preschool have speech and language disorders and a poor communication development, and the need for support is extensive. The aim was to find out if and how reading aloud and storytelling could enhance children's communication development, the study was interactionistic. Eleven municipal preschools with 23 child units (573 children) participated. A questionnaire containing 15 questions with 54 sub-items was answered on group level by the staff. The results showed that reading aloud and storyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 13 publications
0
13
0
15
Order By: Relevance
“…Kemampuan membaca permulaan anaka dalah keterampilan dasar anak pada aspek bahasanya yang dijadikan bekal untuk memasuki perkembangan selanjutnya. Dalam membaca permulaan anak dapat mengenal berbagai bunyi huruf dan kata akan menambah pembendaharaan kata, wawasan pada anak, pemahaman terhadap situasi dan kejadian disekitar, dan dalam lingkup perkembangan keaksaraan (Brodin & Renblad, 2019). (Rahadian, Rohanda, & Anwar, 2014) menjelaskan Kemampuan literasi Bahasa anak terutama dalam kemampuan membaca permulaan terdapat beberapa factor yang mempengaruhinya diantaranya adalah: factor fisiologis, intelektual.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kemampuan membaca permulaan anaka dalah keterampilan dasar anak pada aspek bahasanya yang dijadikan bekal untuk memasuki perkembangan selanjutnya. Dalam membaca permulaan anak dapat mengenal berbagai bunyi huruf dan kata akan menambah pembendaharaan kata, wawasan pada anak, pemahaman terhadap situasi dan kejadian disekitar, dan dalam lingkup perkembangan keaksaraan (Brodin & Renblad, 2019). (Rahadian, Rohanda, & Anwar, 2014) menjelaskan Kemampuan literasi Bahasa anak terutama dalam kemampuan membaca permulaan terdapat beberapa factor yang mempengaruhinya diantaranya adalah: factor fisiologis, intelektual.…”
Section: Pendahuluanunclassified
“…Pembelajaran yang sesuai dengan kebutuhan anak membuat anak tidak merasa terbenani dan merasa sedang tidak membelajarkan sesuatu. (Brodin & Renblad, 2019) menjelaskan salah satu letak kesuksesan anak belajar adalah dengan memposisikan anak dalam situasi dan lingkungan yang kondusif serta ketersediaan model, media serta metode yang sesuai dengan kebutuhan anak. Dengan demikian anak secara cepat menyerap informasi sehingga kegiatan literasi berbahasa membaca permulaan menjadi sesuatu yang meyenangkan bagi anak.…”
Section: %unclassified
“…Empowering children's early language skills with the support of parents can make significant contributions to reducing the possible aggressive behavior of these children. On the other hand, studies in the field revealed that education in preschool institutions contributes positively to language development of children (Brodin & Renblad, 2019;Foorman, Anthony, Seals, & Mouzaki, 2002;Olofsson & Niedersøe, 1999;Taner & Başal, 2005;Tunçeli & Zembat, 2018). From this point of view, parents should not only be able to engage in language-based interactions with their children, but also initiate institutional preschool education.…”
Section: Discussionmentioning
confidence: 99%
“…Penguasaan kosakata dapat memengaruhi keterampilan berbahasa seseorang, begitu juga dengan kemampuan seseorang menggunakan dan mempelajari bahasa banyak dipengaruhi oleh kosakata yang dimilik (Brodin & Renblad, 2019;Menyuk & Brisk, 2005). Bahasa dapat berfungsi kepada seseorang apabila keterampilan berbahasa seseorang meningkat.…”
Section: Pendahuluanunclassified